Effect of dietary protein source on piglet meat quality characteristics (International Journal of Health, Animal Science and Food Safety, 2014)
An experiment was conducted to examine the effects of different dietary protein sources (soybean meal vs whey protein) on piglet meat quality characteristics. Eighteen castrated male Large White × Duroc × Landrace piglets were randomly assigned to 2 groups. Piglets were kept in individual metabolic cages and fed ad libitum over a period of 38 days the following 2 diets: diet SB, which was formulated to meet the nutrient requirements of piglets using soybean meal as the main crude protein source and diet WP, where SB was totally replaced by a mixture of whey proteins on equal digestible energy and crude protein basis. At the end of the experiment, piglets were weighed and slaughtered. After overnight chilling, samples of Longissimus dorsi muscle were taken and were used for meat quality measurements.         No significant differences were observed in the values of pH, colour, water holding capacity, shear force and intramuscular fat content of L. dorsi muscle between the dietary treatments. Measurement of lipid oxidation values showed that dietary supplementation with different protein sources did not influence meat antioxidant properties during refrigerated storage. The SB piglets had lower 14:0 (P
Keywords: soybean meal; whey proteins; piglets; oxidation; meat quality